Chantriolides F–P, Highly Oxidized Withanolides with Hepatoprotective Activity from Tacca chantrieri - Yang, Yue; Zhou, Fei; Wang, Min; Turanazarov, Mukhammadrizo; Wang, Xiao-Rong; Ke, Changqiang; Yao, Sheng; Lin, Ligen; Tang, Chunping; Ye, Yang (Molecules (Basel, Switzerland), 2022)
Eleven highly oxidized withanolides, chantriolides F–P (1–11), together with six known analogues (12–17), were isolated from the rhizomes of Tacca chantrieri. Their structures were established on the basis of comprehensive spectroscopic data analysis and comparison with published NMR data, and their absolute configurations were further confirmed by experimental ECD data and single crystal X-ray diffraction analysis. The structures of compounds 5–8 contained a chlorine atom substituted at C-3. Compounds 1 and 12 are a pair of epimers isomerized at C-24 and C-25, while compounds 9 and 16 are isomerized at C-1, C-7, C-24, and C-25. Next, the hepatoprotective effect of all the isolates was evaluated on tert-butyl hydroperoxide (t-BHP)-injured AML12 hepatocytes. Compounds 5–11 and 16 significantly enhanced cell viability. Compound 8 decreased reactive oxygen species accumulation and increased glutathione level in t-BHP injured AML12 hepatocytes through promoting nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2).